2016
DOI: 10.1016/j.rehab.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of heterotopic ossification after removal in patients with traumatic brain injury: A systematic review

Abstract: The recurrence of NHO is not affected by delayed surgery, neurological sequelae or disease extent around the joint. Surgical excision of NHO should be performed as soon as comorbid factors are under control and the NHO is sufficiently constituted for excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 49 publications
1
36
0
1
Order By: Relevance
“…Altogether, our results suggest that NHO-MDSCs are capable of participating in the formation of HOs in brain injury or SCI patients, as reported with MSCs isolated from battlefield-injured muscle tissue (19). NHOs can relapse, even 15 years after surgery (F. Genet, unpublished observations) (53), and our results indicate that NHO-MDSCs with osteogenic potential are still present in muscles after NHO resection. This hypothesis is strengthened by the recent study by Agarwal et al (54), showing that PDGFRα + MSCs are responsible for HO recurrence in a burn/tenotomy mouse model.…”
Section: Discussionsupporting
confidence: 79%
“…Altogether, our results suggest that NHO-MDSCs are capable of participating in the formation of HOs in brain injury or SCI patients, as reported with MSCs isolated from battlefield-injured muscle tissue (19). NHOs can relapse, even 15 years after surgery (F. Genet, unpublished observations) (53), and our results indicate that NHO-MDSCs with osteogenic potential are still present in muscles after NHO resection. This hypothesis is strengthened by the recent study by Agarwal et al (54), showing that PDGFRα + MSCs are responsible for HO recurrence in a burn/tenotomy mouse model.…”
Section: Discussionsupporting
confidence: 79%
“…Prolonged immobilization is suspected to be a significant factor for HO development [ 25 ]. Studies of the formation of HOs after central neurological lesions have shown that delayed access to a rehabilitation centre is a risk factor [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged immobilization is suspected to be a significant factor for HO development [ 25 ]. Studies of the formation of HOs after central neurological lesions have shown that delayed access to a rehabilitation centre is a risk factor [ 25 ]. Moreover, the paralysis is also considered as a cofounding factor relating to the importance of early mobilization in ICU [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have suggested that connective tissue cells change their characteristics into bone-forming cells as some type of inflammatory reaction to injury. Individuals with other boneforming disorders such as ankylosing spondylitis, Paget disease, and idiopathic skeletal hyperostosis are at the risk for HO following traumatic brain or spinal cord injury (Almangour et al 2016). …”
Section: Definitionmentioning
confidence: 99%